Структурні та електрофізичні властивості точково-контактних сенсорних мультиструктур - Гарбуз, Дмитро Олександрович (My University, 2024)
Дисертаційна робота присвячена розробці методу створення точково-контактних сенсорних матриць з характеристиками, що відтворюються, удосконаленню технології отримання таких нанооб'єктів, проведенню досліджень, що спрямовані на поглиблення розуміння природи точково-контактних сенсорів видихуваного газу на основі сполуки тетраціанохінодіметану, а також розробці методологічної основи для аналізу спектральних сенсорних профілів газу, що видихається, з медичним застосуванням. Робота виконана на кафедрі фізики металів і напівпровідників Національного технічного університету «Харківський політехнічний інститут» та в Фізико-технічному інституті низьких температур (ФТІНТ) ім. Б.І. Вєркіна Національної академії наук України у відділі «Спектроскопії молекулярних систем і наноструктурних матеріалів». Метою даної роботи є поглиблення розуміння природи та особливостей функціонування точково-контактних сенсорів видихуваного газу на основі сполуки тетраціанохінодиметану, розробка методу створення точково-контактних сенсорних матриць з характеристиками, що відтворюються, удосконалення технології отримання таких нанооб'єктів, а також розробка методологічної основи методу аналізу точково-контактних сенсорних профілів складних газових сумішей для медичної діагностики. Об’єкт дослідження – процеси, що відбуваються під час синтезу та функціонування точково-контактних мультиструктур, їх впливу на структуру, морфологію та властивості експериментальних газових сенсорів. Предмет дослідження – особливості структури, росту та фазового складу точково-контактних сенсорів на основі органічних провідників, сигнал відгуку сенсорних матриць на дію складних газових сумішей. The thesis is devoted to the development of a method for creating point-contact sensor matrices with reproducible characteristics, improvement of the technology for obtaining such nano-objects, carrying out studies aimed at deepening the understanding of the nature of point-contact breath sensors based on the tetracyanoquinodimethane compound, as well as the development of a methodological basis of the approach to analyze the spectral sensor profiles of breath for medical purposes. The work was carried out at the Department of Physics of Metals and Semiconductors of the National Technical University "Kharkiv Polytechnic Institute" and at B. Verkin Institute for Low Temperature Physics and Engineering of the National Academy of Sciences of Ukraine at the Department of Spectroscopy of Molecular Systems and Nanostructured Materials. The purpose of the dissertation is the understanding deepening of the nature of breath point-contact sensors based on the tetracyanoquinodimethane compound, development of a method for creating point-contact sensor matrices with reproducible characteristics, improvement of the technology for obtaining such nano-objects, as well as development of a methodological basis for the method of analysis of point-contact sensor profiles of complex gas mixtures for medical diagnostics. The object of the study is the process occurring during the synthesis and functioning of point-contact sensor multistructures, and their influence on the structure, morphology and properties of functional sensors. The subject of the study is features of the structure, growth and phase composition of point-contact sensors based on organic conductors, pecularities of the response of sensor matrices to the action of complex gas mixtures. The introduction substantiates the relevance of the studies performed, formulates the purpose and tasks of the research, defines the object, subject and methods of the research, shows the connection of the work with scientific topics, describes the scientific novelty and practical significance of the obtained results, indicates the personal contribution of the author, provides information about the work approbation and publications of research results obtained.
Structural and electrophysical properties of point-contact sensor multistructures
Keywords: Наноструктура; Наноматеріали; Електропровідність; Рентгенівська дифракція; Морфологія поверхні; Структура; Напівпровідники; Полікристалічні плівки; Точкові контакти; Видихуваний газ; Газові сенсори; Низьковимірні системи; Кристалічні тверді тіла; Фазовий склад; Геометрія; Nanostructure; Nanomaterials; Electrical conductivity; X-ray diffraction; Surface morphology; Structure; Semiconductors; Polycrystalline films; Point contacts; Breath gas; Gas sensors; Low-dimensional systems; Crystalline solids; Phase composition; Geometry